Sexuality in Persons With Hidradenitis Suppurativa: Factors Associated With Sexual Desire and Functioning Impairment - Quinto, Rossella Mattea; Mastroeni, Simona; Sampogna, Francesca; Fania, Luca; Fusari, Roberta; Iani, Luca; Abeni, Damiano (Frontiers in Psychiatry, 2021)
Hidradenitis Suppurativa (HS) is a chronic skin disease involving intimate and sensitive areas and affecting physical and mental health. We investigated the prevalence of sexual desire and functioning impairment, and their associations with quality of life, anxiety, depression, minor psychiatric disorders (MPD), and clinical features (e.g., disease severity) in 77 patients with HS who completed self-report measures and answered to questions assessing socio-demographic characteristics, lifestyle habits, and hindered sexuality due to HS. The majority of patients reported hindered sexuality, and poor sexual functioning, while showing good levels of dyadic and solitary sexual desire. No associations were found between clinical severity and sexuality measures. Multivariate analyses showed significant associations of sexual outcome measures with alcohol consumption, low Body Mass Index, family history of HS, and severe skin symptoms. Moreover, we found that the presence of negative psychological factors (i.e., MPD, anxiety, poor mental status) increased the risk of sexual impairment. These findings underline the important role of psychological and sexual aspects in HS patients and suggest that physicians should consider the effect of disease burden on patients’ sexual health.